HIV and aging: insights from the Asia Pacific HIV Observational Database (APHOD). Issue 3 (18th November 2014) - Han, N; Wright, ST; O'Connor, CC; Hoy, J; Ponnampalavanar, S; Grotowski, M; Zhao, HX; Kamarulzaman, A; Australian HIV Observational Database (AHOD); TREAT Asia HIV Observational Database (TAHOD)
<x xml:space="preserve">Abstract</x> Objectives The proportion of people living with HIV/AIDS in the ageing population (> 50 years old) is increasing. We aimed to explore the relationship between older age and treatment outcomes in HIV‐positive persons from the Asia Pacific region. Methods Patients from the Australian HIV Observational Database (AHOD) and the TREAT Asia HIV Observational Database (TAHOD) were included in the analysis. We used survival methods to assess the association between older age and all‐cause mortality, as well as time to treatment modification. We used regression analyses to evaluate changes in CD4 counts after combination antiretroviral therapy (cART) initiation and determined the odds of detectable viral load, up to 24 months of treatment. Results A total of 7142 patients were included in these analyses (60% in TAHOD and 40% in AHOD), of whom 25% were > 50 years old. In multivariable analyses, those aged > 50 years were at least twice as likely to die as those aged 30–39 years [hazard ratio (HR) for 50–59 years: 2.27; 95% confidence interval (CI) 1.34–3.83; HR for > 60 years: 4.28; 95% CI 2.42–7.55]. The effect of older age on CD4 count changes was insignificant (p‐trend = 0.06). The odds of detectable viral load after cART initiation decreased with age (p‐trend = < 0.0001). The effect of older age on time to first treatment modification was insignificant (p‐trend = 0.21). We found no statistically significant differences in outcomes between AHOD and TAHOD participants for all endpoints examined. Conclusions The associations between older age and typical patient outcomes in HIV‐positive patients from the Asia Pacific region are similar in AHOD and TAHOD. Our data indicate that 'age effects' traverse the resource‐rich and resource‐limited divide and that future ageing‐related findings might be applicable to each setting.